Evaluasi Kekuatan Struktur Gedung Bertingkat Terhadap Pengaruh Beban Gempa Menggunakan Analisis Dinamik Respon Spektrum (Studi kasus: Gedung MAN Insan Cendikia, Serpong) - Restiawan, Arie Dwie; Bayzoni, Bayzoni; Husni, Hasti Riakara; Isneini, Mohd (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Indonesia is a region that is at risk of earthquakes. The impact of an earthquake is bad for the building structure, not only causing damage to the building, but also can cause the building to collapse. Therefore, to reduce the adverse effects obtained from earthquakes, it is necessary to design and evaluate the strength of building structures with resistance to earthquake loads. The method used in this study is dynamic response spectrum analysis to obtain the magnitude of the earthquake load. Evaluation of the strength of the building structure is carried out using structural analysis software to make it easier to do the analysis. This study aims to determine the ratio of the required strength in conditions without earthquake loads and conditions due to earthquake loads to the designed strength of the structure. Based on the results of this study, it can be concluded that the required strength obtained in conditions without an earthquake load reaches 8.33% to 90.62% of the designed strength, whereas in conditions due to strong earthquake loads the required strength obtained reaches 12.57% to 153.31% of the designed strength.Keywords: earthquakes, structural strength, dynamic analysis, response spectrum.